Linking macrophyte community structure with food chain length: A case study in the largest freshwater lake in China and ecological restoration implications - Yuhan He (Elsevier, 2021)
Food chain length is a significant ecosystem index and it greatly affects ecosystem processes and their outcomes. In recent decades, determinants or indicators of FCL have been investigated in different ecological contexts, but few studies analyzed the relationships between macrophyte community structure and the food chain length of freshwater ecosystems despite the crucial role of macrophyte community in determining food web structure. This study investigated the influence of macrophyte community structure on food chain length by conducting a field survey in Lake Poyang, the largest freshwater lake in China. Plant volume inhabited (PVI), Shannon-Wiener diversity index and Pielou’s evenness index were used to indicate macrophyte community structure. Our results suggested that intermediate levels of PVI and diversity (PVI 44% and diversity 0.61) with greater evenness could support longer food chain in sub-lakes of Lake Poyang. We proposed that macrophyte community structure indexes could be useful indicators in indicating food chain length in freshwater ecosystem. These novel findings also highlight that within suitable ranges of PVI and diversity, better restoration effect could be achieved by higher macrophyte evenness in lake management. Our findings provide new insights for the restoration and management of macrophytes in freshwater ecosystems.